2018
DOI: 10.1007/s10238-018-0519-0
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase-4(DPP-4) inhibitors: promising new agents for autoimmune diabetes

Abstract: Dipeptidyl peptidase-4 (DPP-4) inhibitors constitute a novel class of anti-diabetic agents confirmed to improve glycemic control and preserve β-cell function in type 2 diabetes. Three major large-scale studies, EXAMINE, SAVOR-TIMI 53, and TECOS, have confirmed the cardiovascular safety profile of DPP-4 inhibitors. Based on these results, DPP-4 inhibitors have gained widespread use in type 2 diabetes treatment. It is currently unknown, however, whether DPP-4 inhibitors have similar therapeutic efficacy against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 107 publications
0
28
0
Order By: Relevance
“…In addition, it is important to recognize the presence of autoimmunity as a means to attain optimal metabolic control and preserve β‐cell function to decrease the risk of long‐term diabetes complications. In this regard, recent progress has been made through specific treatment with dipeptidyl peptidase 4 inhibitors to protect C‐peptide levels and improve glycemic control in LADA patients …”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is important to recognize the presence of autoimmunity as a means to attain optimal metabolic control and preserve β‐cell function to decrease the risk of long‐term diabetes complications. In this regard, recent progress has been made through specific treatment with dipeptidyl peptidase 4 inhibitors to protect C‐peptide levels and improve glycemic control in LADA patients …”
Section: Discussionmentioning
confidence: 99%
“…Secreted from the L cells of the intestines finishing meals, GLP-1 acts on increasing glucose-dependent insulin secretion from β-cells and inhibiting glucagon release. Additionally, it could also retard gastric emptying and promote satiety by function of the brain ( Wang et al, 2018 ). The predominant glucose-lowering impact of DPP-4 inhibitors is mediated by inhibiting the activity of DPP-4.…”
Section: Drug Therapymentioning
confidence: 99%
“…DPP-4 inhibitors have been highlighted as potential regimen for autoimmune-disease based on the characteristics in T-cell activation and inflammation. 55 Notably, autoimmune animal model becomes a platform for testing in vivo efficacy of DPP-4 inhibitors in long-term administration. 114 Alternatively, in vivo assay of DPP-4 inhibitory efficacy can be verified by diabetic animal model despite the fact that DPP-4 can degrade GLP-1, leading to insulin desensitization and secretion decrease.…”
Section: Methods For Screening Novel Dpp-4 Inhibitorsmentioning
confidence: 99%
“…69 In addition, it has been suggested that sitagliptin can preserve pancreatic β-cell function and subsequently stabilize insulin secretion as shown by two 4-year clinical trials, in which sitagliptin was adopted to treat slowly progressive type 1 DM (SPTIDDM) and latent autoimmune diabetes adult (LADA). 55,70 In addition to clinical treatment, DPP-4 levels can be used as a biomarker. For instance, high serum sDPP-4 levels can be referred to the elevated glycation end products, which subsequently evoke endothelial cell damage and diabetic nephropathy incidence.…”
Section: Overview Of Dpp-4 and Its Biological Functionmentioning
confidence: 99%